Nanotechnology: A Promising New Paradigm for the Control of Pain. Issue 2 (27th June 2017) - Chakravarthy, Krishnan V; Boehm, Frank J; Christo, Paul J
Abstract: Objective: The objective of this article is to critically review both preclinical and clinical studies that focus on the use of nanotechnology for both acute and chronic pain management, surveying both diagnostic and therapeutic applications. The article also provides information on nanotechnology for pain practitioners, so that they may better understand how this technology works and how it may be applied to their day-to-day clinical practice. Study Design: Narrative review. Methods: The Pubmed NCBI and EMBASE databases were utilized to review published reports of in vivo and clinical studies that focus on using nanotechnology for pain management applications in both the acute and chronic pain settings. Results: Articles were screened by title, abstract, and full article review. They were then analyzed by specific clinical indications, and appropriate data were presented based on a critical analysis of those articles. Conclusions: As the development of nanomedical applications in acute and chronic pain management continues, medical practitioners should consider their growing potential to enhance the care of patients who are consistently living with pain. Current barriers to implementation include manufacturing scale-up for commercial viability, long-term nanoparticle toxicity considerations, and high cost for successful passage through clinical trials. These challenges will need to be overcome with ongoing translational research efforts in collaboration with industry and government bodies such as the Food and Drug Administration (FDA).